Asylum hotel : a novel [large type] - Blackwell, Juliet (Center Point Large Print, 2025)
"Aubrey Spencer loves photographing classic buildings and abandoned places that hold old secrets. The Hotel Seabrink, perched overlooking the sea, is one such place. Currently abandoned but scheduled for a major renovation, it has a torrid history. Back in the 1920s it hosted A-list celebrity clientele, and now the locals insist it is haunted by the ghosts of two young women who died there. When Aubrey goes to photograph the site before the renovation begins, she bumps into a man named Dimitri Petroff, a minor online celebrity who shares her fascination with old buildings, the Hotel Seabrink in particular. When he is found dead the next day at the base of a cliff, the police are quick to close the investigation. But Aubrey feels unsettled by locals who claim he was murdered and that it's not the first time someone interested in the hotel was killed. As she digs deeper into the property's dark history (and its origins as an asylum) as well as Dimitri's professional rivalries, she becomes mired in an unsolved murder case from several decades earlier, one with eerie parallels to the contemporary case. But someone is determined to keep her from discovering the truth-at any cost."--